Les politiques méditerranéennes de l'Espagne à la recherche d'un équilibre entre l'impératif de la sécurité et l'éthique de l'interdépendance (Note) - Labatut, Bernard (Études internationales, 1995)
Franco's Spain flattered itself as enjoying a preferential relationship with the Arab World, as with Latin America as well - a kind of compensation for Spain's lack of normalization within the international System. With its transition to democracy, Spain's place in the world has been redefined and, consequently, so have its relations in the Mediterranean. This has taken place in a context made difficult by Spain's integration into European and Western institutions, an integration that holsters it but no longer lets it take advantage of its different status. This redefinition has also occurred as Spain faces increased risks of destabilization from countries along the southern shoreline, which pose a very direct security problem for Spain. The policies it has implemented expose the divisions between several kinds of logic. They also reveal the many constraints Spain must face in a region split along different lines and in which it finds itself completely immersed.